An Analysis of Code Mixing Used by Teacher - Agustinus Manalu (elt, 2020)
ABSTRACT This thesis was aimed to find the type of code mixing used by teacher during classroom interaction. The study used descriptive qualitative method. Each sentence from the teacher and students conversation was identified to determine its code mixing type according to Hoffman’s theory (1991). The data of the study is utterances which code mixing is included in it. The technique of the data collections used is documentary technique. It is found that there were three types of code mixing used during the class according to Hoffman theory namely : (1) intra-sentential, (2) intra-lexical, (3) involving change of pronunciation. From those types, intra-sentential was most frequently used by the teacher during the process of teaching and learning. The teacher`s reasons for applying code mixing were to overcome the communication barriers that occur between the teacher and the students to help the students understand and memorize the material more accessible. The result of the interview also showed that the students had a good perception of the implementation of code mixing used by the teacher in the classroom. Keyword : code mixing, intra-sentential, classroom interaction, teacher